2017
DOI: 10.1177/0969733017720847
|View full text |Cite
|
Sign up to set email alerts
|

A concept analysis of professional commitment in nursing

Abstract: There is a need for continuous advancement in the development of the concept, specific actions to encourage this and the improvement of evaluation methods for its study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 37 publications
(66 reference statements)
0
24
0
1
Order By: Relevance
“…Additionally, these values are frequently not covered throughout the nursing curriculum in the depth students require [33]. Furthermore, Garcia-Moyano et al [26] pointed out the fact that understanding the very concept of professional values might result in some ambiguity when it comes to actual nursing practice. In this regard, MacDonnell and Buck-McFadyen's study [34] demonstrated how managing this would call for a reorientation of nursing practice by including political action, which is important for improving people's lives and is an integral component of nurses' professional practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these values are frequently not covered throughout the nursing curriculum in the depth students require [33]. Furthermore, Garcia-Moyano et al [26] pointed out the fact that understanding the very concept of professional values might result in some ambiguity when it comes to actual nursing practice. In this regard, MacDonnell and Buck-McFadyen's study [34] demonstrated how managing this would call for a reorientation of nursing practice by including political action, which is important for improving people's lives and is an integral component of nurses' professional practice.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the acquisition of such values typically occurs through role modeling and clinical practice [23,24], through the inclusion of the values within the curriculum [14] and facilitating the acquisition of values [25]. Furthermore, the incorporation of professionalism and its evaluation within undergraduate training has been gaining momentum [26], which might help to address some of these issues more effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, further research is required to confirm the causal relationship. In addition, Garcı’a-Moyano et al believed that in order to promote the formation of nursing professional commitment, besides material resources (such as rewards and salary) we need to increase more personal motivation for professional development and cultivate actual professionals in nursing [ 46 ]. Cheng et al pointed out that newly graduated male nurses are often concerned about their lack of ability and doubt whether they are suitable for nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that nursing care is provided with higher quality in hospitals where nurses work with a high professional commitment [14][15][16]. Garcia-Moyano et al reported that nurses' professional commitment increases the quality of care and safety and patients' satisfaction, as well as increases nurses' professional ability and decision-making [17].…”
Section: Introductionmentioning
confidence: 99%